PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 4 PONTIANAK - Herwati, Neti (Universitas Tanjungpura, 2020)
This research is aimed to improve the pedagogical competence of teachers at SMP Negeri 4 Pontianak. This research was conducted in two cycles, in each cycle having planning, implementation, observation and reflection. Data analysis techniques that guide data management by using a percentage (%) to achieve a constant of 100. A maximum score of 92 out of seven pedagogical competencies consisting of; Competency 1; Get to know the characteristics of students. Competency 2; Mastering learning theory and principles of learning. Competency 3; Curriculum Development. Competency 4: Educating learning activities. Competency 5; Understand and develop potential. Competency 6; Communication with students. Competency 7: Assessment and evaluation. Research Results in the first cycle the lowest value of 70% and in thesecond cycle the lowest value of 80%. The highest average value in cycle I was 79% and the highest average value in cycle II was 84%. There is an increase in percentage of teacher pedagogical competence through academic supervision by 5% from cycle I.